Probing the putative role of imprinted Begain in the modulation of neuropathic pain - Joana Inês Alves Faria (2022)
Neuropathic pain is a complex pain condition that generally results from a somatosensory system lesion or disease. Begain is a protein highly expressed on the nervous system thought to interact with the NMDA receptor through the PSD-95/SAP90 protein and to be recruited to synapses dependent on NMDAR activity. Mice were subjected to peripheral nerve injury-induced neuropathic pain and the Von Frey test was used to assess mechanical allodynia. Behavior analysis showed that the genotype-dependent allodynia induced by SNI is not significantly affected by the mutation on imprinted Begain 1B. The expression of the Begain1B isoform was unaffected by the SNI model. Nevertheless, the expected genotype effect was evident, showing full silencing in KO mice and a significant downregulation in Het Pat animals as compared to Het Mat or WT mice. Concerning the imprinting, Begain 1B and Dlk1 exhibited paternal expression in SC and RVM consistent with their classically described parental expression. The Begaintm1bMLS model's preliminary findings suggest that it will be a useful tool for integrating the control of imprinted genes by epigenetic mechanisms in pathological contexts. Extensive research however is required to better understand the role of the begain 1B isoform in the latter stages of pain chronification.